Treatment for Spontaneous Intracranial Dissecting Aneurysms in Childhood: A Retrospective Study of 26 Cases - Zhang, Yi-Sen; Wang, Shuo; Wang, Yang; Tian, Zhong-Bin; Liu, Jian; Wang, Kun; Chen, Jun-Fan; Yang, Xin-Jian (Frontiers in Neurology, 2016)
Objective This study aimed to assess the clinicoradiological features and treatment outcome of intracranial dissecting aneurysms (IDAs) in childhood. Methods We conducted a retrospective study of pediatric patients who were treated for spontaneous IDAs in our institute between January 2010 and December 2015. The clinical presentation, aneurysm characteristics, treatment modality, and outcome were studied. Results We studied 26 pediatric patients (mean age, 13.4 years; range, 4–18 years) with 31 IDAs who comprised 6.9% of all IDA patients treated during the same period. Seventeen (65.4%) patients were male and nine (34.6%) were female. The incidence of large (≥10mm in size) or giant aneurysms (≥25mm in size) was 65.5%. Twenty-one (80.8%) patients underwent endovascular or surgical treatment and five (19.2%) received conservative treatment. Perioperative complications occurred in three patients, in whom two eventually recovered completely with a Glasgow Outcome Scale (GOS) score of 5 and one partially recovered with a GOS score 4. Overall, 25 (96.2%) patients had a favorable outcome and one (3.8%) had an unfavorable outcome at a mean follow-up of 22.8 months (range, 6–60 months). Conclusions Pediatric IDAs are rare. In this series, endovascular management was a relatively safe and effective method of treatment for pediatric IDAs. However, continued follow-up is required because of the possibility of aneurysm recurrence and de novo aneurysm formation after treatment.